A nationwide assessment of litter on China's beaches using citizen science data. (March 2020) - Chen, Hongzhe; Wang, Sumin; Guo, Huige; Lin, Hui; Zhang, Yuanbiao
Abstract: China is the largest plastic consumer in the world. Despite its plastic waste import ban in 2017, this populous economy inevitably generates a large amount of waste, including plastic waste, a considerable part of which has become marine litter. Data from the 2018 National Coastal Cleanup and Monitoring Project, the largest beach litter monitoring activities using the citizen science approach in China, have been retrieved and analyzed to understand spatial patterns, composition, and original usage of marine litter. Within this project, 24 beaches were surveyed every two months. As a result, the mean density was 3.85 ± 5.39 items m −2, much higher than that reported by previous studies in China. There were great differences in the spatial distribution of litter. The highest densities appeared in the runoff-affected area of the Yangtze River, which was another difference from previous studies. Low-density, easy-to-transport foamed plastics were the major contributor to marine litter in these areas. Along China's coast, approximately 90% of litter was from land-based sources, and over half of that originated from domestic sources. Including foamed plastic products, plastic litter with low recycling value dominated. Both natural and human factors influencing the spatiotemporal distribution and composition of litter are discussed. Socioeconomic factors, such as the lifestyle and consumption levels of citizens and local waste management systems, are possible explanations for the low-value characteristic of marine litter. The deviation between previous data and citizen science data in this study may be caused by many factors. Based on the discussion on these factors, some suggestions for citizen science research in China are also put forward. Graphical abstract: Image 1 Highlights: Litter densities from citizen science were higher than previous studies in East Asia. The maximum site-mean density was ∼136 times the minimum one. Large runoffs strongly affect the distribution of beach litter. Low-density, easy-to-migrate foamed plastics prevailed in runoff-affected areas. Low value for recycling was a main litter characteristic along the whole coast. Abstract : Low value for recycling was a main litter characteristic along the coast, while foamed plastics prevailed in Yangtze River runoff-affected areas.